Guidelines for Healthy Spaces Developing in areas of Mueang Suphan-buri District, Suphan-buri Provin: Guidelines for Healthy Spaces Developing in areas of Mueang Suphan-buri District, Suphan-buri Provin - Wannanurak, Sodtipat; Taesoongnorn, Anuchid; Akatwiphat, Thammarat; Hongsombud, Sasipimmas (RATANABUTH JOURNAL, 2026)
This research aimed to: 1) investigate the utilization behaviors of sports grounds for health promotion among people in Mueang District, Suphan Buri Province; 2) examine the demand for health-promoting space services among the population in the same area; and 3) develop guidelines for developing health-promoting spaces in Mueang District, Suphan Buri Province. The study employed a mixed-methods research design. The quantitative sample consisted of 395 local residents determined by Taro Yamane’s formula and selected via stratified random sampling. The research instrument was a questionnaire, and the collected data were analyzed using percentage, mean, and standard deviation. For the qualitative strand, data were collected through semi-structured interviews with 15 key informants, including community leaders, local sages, and subdistrict administrative organization officials. The qualitative data were analyzed using inductive content analysis. The research findings revealed that: 1) Overall, the behavior regarding the utilization of sports grounds to promote holistic well-being was at a moderate level. Interestingly, spiritual well-being yielded the highest mean score, whereas physical well-being received the lowest, indicating that these sports grounds functioned as social and spiritual hubs rather than merely physical exercise areas. 2) Regarding user needs, the overall demand for well-being space services was at a high level, with the physical dimension ranking the highest. 3) The context-specific development guidelines for each subdistrict were as follows: (1) Sanam Chai focused on prioritizing the resurfacing of uneven sports fields and offering a diverse range of multi-sport equipment; (2) Thap Ti Lek emphasized infrastructure improvement, particularly night-time safety lighting systems and hygienic restrooms; and (3) Bueng Ban Pho highlighted facility organization, rest areas, clean energy integration (solar cells), and proactive event-driven health activities.